Student movements for multiculturalism : challenging the curricular color line in higher education - Yamane, David (Johns Hopkins University Press, 2001)
Beginning with the premise that a comprehensive understanding of American life must confront the issue of race, sociologist David Yamane explores efforts by students and others to address racism and racial inequality - to challenge the color line - in higher education. By 1991, nearly half of all colleges and universities in the United States had established a multicultural general education requirement. Yamane examines how such requirements developed at the University of California at Berkeley and the University of Wisconsin at Madison during the late 1980s, when these two schools gained national attention in debates over the curriculum. Based on interviews, primary documents, and the existing literature on race and ethnic relations, education, cultural conflict, and the sociology of organizations, Student Movements for Multiculturalism makes an important contribution to our understanding of how curricular change occurs and concludes that multiculturalism represents an opening, not a closing, of the American mind.